Prospects for corporate sustainable development in the context of post-crisis recovery - Berlizova, Viktoriia (Theory and Practice of Public Administration, 2026)
The conditions of post-crisis recovery, complicated by global economic shocks, wartime risks, social transformations, and the intensification of environmental problems, require a fundamental review of traditional corporate strategies. Ensuring the long-term competitiveness and resilience of corporations is impossible without the implementation of sustainable development principles and ESG criteria. In this regard, the aim of the article is to substantiate the theoretical and practical foundations for shaping the prospects of sustainable corporate development in the context of post-crisis economic recovery, considering ESG approaches and modern challenges. The application of interdisciplinary, systemic, and structural-functional approaches allowed for viewing the corporation as an integrated and adaptive socio-economic system. The article presents a comprehensive study of the key directions of corporate strategy transformation, highlighting the shift from short-term profit maximization to the concept of creating long-term shared value. The decisive role of ESG approaches, digitalization of business processes, effective corporate governance, and innovative anti-crisis strategies in ensuring corporate stability is proven. The organizational, economic, institutional, and information-analytical mechanisms for implementing sustainable development strategies are systematized. The main scientific achievement is the development of a conceptual model for the sustainable development of a corporation under post-crisis recovery conditions, which comprehensively reflects the interconnections among the external environment, the anti-crisis management subsystem, and integrating ESG tools. The findings and the developed model provide an applied foundation for transforming the corporate sector in the post-war period. It is demonstrated that the integration of the proposed approaches is critically important for attracting ESG investments into the restoration of energy, infrastructure, and transport sectors. The implementation of the defined priority directions will contribute to increasing the investment attractiveness of corporations, reducing risks, building public trust, and harmoniously combining economic growth with environmental protection.